Evolutionary history of the European free‐tailed bat, a tropical affinity species spanning across the Mediterranean Basin. (25th November 2019) - Amorim, Francisco; Razgour, Orly; Mata, Vanessa A.; Lopes, Susana; Godinho, Raquel; Ibáñez, Carlos; Juste, Javier; Rossiter, Stephen J.; Beja, Pedro; Rebelo, Hugo
Abstract: The Mediterranean Basin is a global biodiversity hotspot, hosting a number of native species belonging to families that are found almost exclusively in tropical climates. Yet, whether or not these taxa were able to survive in the Mediterranean region during the Quaternary climatic oscillations remains unknown. Focusing on the European free‐tailed bat ( Tadarida teniotis ), we aimed to (a) identify potential ancient populations and glacial refugia; (b) determine the post‐glacial colonization routes across the Mediterranean; and (c) evaluate current population structure and demography. Mitochondrial and nuclear markers were used to understand T. teniotis evolutionary and demographic history. We show that T. teniotis is likely restricted to the Western Palearctic, with mitochondrial phylogeny suggesting a split between an Anatolian/Middle East clade and a European clade. Nuclear data pointed to three genetic populations, one of which is an isolated and highly differentiated group in the Canary Islands, another distributed across Iberia, Morocco, and France, and a third stretching from Italy to the east, with admixture following a pattern of isolation by distance. Evolutionary and demographic reconstruction supports a pre‐Last Glacial Maximum (LGM) colonization of Italy and the Anatolian/Middle East, while the remaining populations were colonized from Italy after the Younger Dryas. We also found support for demographic expansion following the Iberian colonization. The results show that during the LGM T. teniotis persisted in Mediterranean refugia and has subsequently expanded to its current circum‐Mediterranean range. Our findings raise questions regarding the physiological and ecological traits that enabled species with tropical affinities to survive in colder climates. Abstract : European free‐tailed bat populations were able to survive in Italy and Anatolia/Middle East during the LGM and have subsequently colonized the current species range. Phylogenetic reconstruction confirms a split of two main lineages, Anatolian/Middle East clade and a European clade further splitting into two subgroups. One of the groups in the European clade is exclusive to Iberia and Morocco while the other is distributed elsewhere in central and western Mediterranean. Population structure analysis revealed three main genetic populations with meaningful gene flow.